2019
DOI: 10.1097/sla.0000000000003637
|View full text |Cite
|
Sign up to set email alerts
|

Survival After Robotic-assisted Prostatectomy for Localized Prostate Cancer

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
(95 reference statements)
0
4
0
Order By: Relevance
“…The result was similar with a previous study reporting that the all-cause mortality was 3.9%. [36] However, the cancer-specific mortality was lower than previous reports (1.7% and 4.3%). [37,38] This might be due to the higher surgical volume at our center and higher level of experience because we excluded patients from the learning curve period of the first two years of surgery performed by our teams.…”
Section: Plos Onementioning
confidence: 56%
“…The result was similar with a previous study reporting that the all-cause mortality was 3.9%. [36] However, the cancer-specific mortality was lower than previous reports (1.7% and 4.3%). [37,38] This might be due to the higher surgical volume at our center and higher level of experience because we excluded patients from the learning curve period of the first two years of surgery performed by our teams.…”
Section: Plos Onementioning
confidence: 56%
“…11,36,37 Though it is possible that for some patients RARP may afford better perioperative outcomes which may then be associated with improved overall survival compared to ORP, evidence generated by high-quality Randomized Clinical Trials (RCTs) with long-term follow-up is not available. 38 There is an abundance of evidence in the literature related to racial and ethnic disparities in prostate cancer diagnosis, treatment, and outcomes-especially for non-Hispanic Black patients. 39,40 Non-Hispanic Black patients have higher incidence of prostate cancer and are more likely to present with metastases than non-Hispanic White patients.…”
Section: Discussionmentioning
confidence: 99%
“…HVHs use RARP much more often than low‐volume hospitals (LVHs), making the use of RARP a possible surrogate for the volume‐outcome relationship which has been described extensively in the literature 11,36,37 . Though it is possible that for some patients RARP may afford better perioperative outcomes which may then be associated with improved overall survival compared to ORP, evidence generated by high‐quality Randomized Clinical Trials (RCTs) with long‐term follow‐up is not available 38 …”
Section: Discussionmentioning
confidence: 99%
“…From 2003 to 2007, the proportion of minimally invasive procedures (including LRP and RARP) for RP in the United States rose sharply from 4.9% to 44.5%, while RRP dropped from 89.4% to 52.9% ( 3 ). So far, many studies have suggested that RARP can achieve positive surgical margins (PSM) rate as low as LRP, and it has shown advantages over LRP in intraoperative blood loss (188.0 mL), intraoperative blood transfusion rate (1.8%), and average postoperative hospital stay (4 days) ( 4 , 5 ). While improving the incidence of perioperative complications, RARP reduces the proportion of long-term urinary incontinence to about 9%, which is better than open surgery [odds ratio (OR) =1.53] and LRP (OR =2.39) ( 6 ).…”
Section: Introductionmentioning
confidence: 99%